2019
DOI: 10.1128/aem.00086-19
|View full text |Cite
|
Sign up to set email alerts
|

Potential for Microbially Mediated Natural Attenuation of Diluted Bitumen on the Coast of British Columbia (Canada)

Abstract: Western Canada produces large amounts of bitumen, a heavy, highly weathered crude oil. Douglas Channel and Hecate Strait on the coast of British Columbia are two water bodies that may be impacted by a proposed pipeline and marine shipping route for diluted bitumen (dilbit). This study investigated the potential of microbial communities from these waters to mitigate the impacts of a potential dilbit spill. Microcosm experiments were set up with water samples representing different seasons, years, sampling stati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 30 publications
(16 citation statements)
references
References 67 publications
0
16
0
Order By: Relevance
“…However, all these studies, including this one, present some level of variation between successional patterns over time which reinforce the hypothesis that early and late microbial community assemblages are influenced by both deterministic and stochastic processes (Dini‐Andreote et al, ). However, when putting these taxonomic profiles in context with their corresponding oil degradation rates (Tremblay et al, ) Schreiber et al ., ), it appears that regardless of which oil degrading microbes are present, oil is being degraded.…”
Section: Resultsmentioning
confidence: 99%
See 2 more Smart Citations
“…However, all these studies, including this one, present some level of variation between successional patterns over time which reinforce the hypothesis that early and late microbial community assemblages are influenced by both deterministic and stochastic processes (Dini‐Andreote et al, ). However, when putting these taxonomic profiles in context with their corresponding oil degradation rates (Tremblay et al, ) Schreiber et al ., ), it appears that regardless of which oil degrading microbes are present, oil is being degraded.…”
Section: Resultsmentioning
confidence: 99%
“…West coast sampling and microcosm experiments are described in a submitted manuscript by our group (Schreiber et al ., ). To provide context for the current article, excerpts from the Schreiber et al .…”
Section: Methodsmentioning
confidence: 97%
See 1 more Smart Citation
“…However, since no nutrients were added to the sea water for our weathering studies, low rates of biodegradation of the tested oil products were expected based on the results of previous studies [34,35]. Of the climatic parameters assessed it has been reported that temperature affects the rates of biodegradation of oils [36][37][38]. A recent study suggests that the biodegradation of AWB is limited in cold water (ca.…”
Section: Multiple Correlation Analysismentioning
confidence: 97%
“…The authors noted a significant shift to smaller oil droplets, contributing this observation to the energetic movement of copepod appendages when swimming and feeding (mechanically separating oil droplets), and to the ingestion/egestion of oil after being mistaken for prey. Schreiber et al (2019) focused on microbial degradation of diluted bitumen under various conditions (i.e. summer,…”
Section: Toxicity Of Chemically Dispersed Fuel Oilsmentioning
confidence: 99%